IMPROVING STUDENTS’ ACHIEVEMENT IN SPEAKING THROUGH PAIRED STORYTELLING TECHNIQUE - Prame Kardo Siambaton (Universitas Negeri Medan, 2012)
This study attempted to improve students’ achievement through Paired Storytelling Technique. This study was conducted by using Classroom Action Research. The subject of the research was class XI IA 1 SMA Katolik Sibolga which consisted of 42 students, but in calculating the score, only 23 students were taken. The research was conducted in two cycles, cycle I consisted of four meetings and cycle II consisted of two meetings. The instruments for collecting data were quantitative data (speaking test) and qualitative data (diary notes, observation sheet and interview sheet). Based on speaking test’ scores, most of students’ score in accent, grammar, vocabulary, fluency and comprehension kept improving in every test. Based on diary notes, observation sheet, questionnaire and interview, it was found that students were interested in applying Pair Storytelling Technique because it helped the students in improving their speaking achievement. The result of the research showed that Paired Storytelling can improve students’ speaking achievement. Key Words: Improving, Achievement, Speaking, Paired, Storytelling